Organic Facies: Palynofacies and Organic Geochemistry Approaches - Filho, João Graciano Mendonça; Menezes, Taíssa Rêgo; Mendonça, Joalice de Oliveira; Oliveira, Antonio Donizeti de; Silva, Tais Freitas da; Rondon, Noelia Franco; Silva, Frederico Sobrinho da (IntechOpen, 2012)
None